2020
DOI: 10.1101/2020.01.24.918094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyamine metabolism regulates the T cell epigenome through hypusination

Abstract: We report here a central role for polyamines in T cell differentiation and function. Deficiency in ornithine decarboxylase (ODC), a critical enzyme for polyamine synthesis, resulted in a profound failure of CD4 + T cells to adopt correct subset specification, underscored by ectopic expression of multiple cytokines and lineagedefining transcription factors across T H 1, T H 2, T H 17, and T reg polarizing conditions, and enhanced colitogenic potential. T cells deficient in deoxyhypusine synthase (DHPS) or deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Interfering with de novo polyamine synthesis or inhibiting the hypusination of eIF5A was detrimental to NK cell OXPHOS as has been also shown in macrophages [7]. CD4 + T cells lacking either ODC or either enzyme in the hypusination pathway (DHPS or DOHH) had reduced levels of TCA cycle metabolites, suggesting impaired mitochondrial metabolism [6]. Indeed, hypusination of eIF5A is required for the specific translation of certain mitochondrial proteins in macrophages [7].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Interfering with de novo polyamine synthesis or inhibiting the hypusination of eIF5A was detrimental to NK cell OXPHOS as has been also shown in macrophages [7]. CD4 + T cells lacking either ODC or either enzyme in the hypusination pathway (DHPS or DOHH) had reduced levels of TCA cycle metabolites, suggesting impaired mitochondrial metabolism [6]. Indeed, hypusination of eIF5A is required for the specific translation of certain mitochondrial proteins in macrophages [7].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, whether differences in extracellular abundances of polyamines have any effects on NK cells in vivo is an interesting unanswered question. This study in T cells showed that a mechanism linking polyamines to cytokine production involved polyamines impacting upon on epigenetic regulation of the T cells [6]. Interestingly, one outcome of NK cells using the citrate malate shuttle to fuel OXPHOS is the generation of cytosolic acetyl‐CoA that may be important for histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the importance of polyamines was described for several immune cell types. Polyamines were described to accumulate in NK cells and in CD4+ T cells following activation from naïve state [ 13 , 14 ] and this accumulation was shown to be required for appropriate effector function. In IL4 activated macrophages, blocking of polyamine biosynthesis blunted their activation [ 15 ].…”
Section: Resultsmentioning
confidence: 99%